2012
DOI: 10.1007/s00247-012-2484-1
|View full text |Cite
|
Sign up to set email alerts
|

Doppler US measurement of the superior mesenteric artery blood flow in children and adolescents

Abstract: We found that superior mesenteric artery blood flow is significantly lower in children than in adolescents and is associated with body surface area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Values of SMA BFV were low in all patients when assessed according to the formulas given in the studies by Eloi et al (6) and Van Bel et al (7). PSV values, except in one patient, and RI values were also low according to the normal values given in the study by Okada et al (8) EDV values of all patients were in normal limits.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Values of SMA BFV were low in all patients when assessed according to the formulas given in the studies by Eloi et al (6) and Van Bel et al (7). PSV values, except in one patient, and RI values were also low according to the normal values given in the study by Okada et al (8) EDV values of all patients were in normal limits.…”
Section: Resultsmentioning
confidence: 77%
“…A literature review revealed that CDUS examination of the SMA has been used to determine Crohn disease activity or intestinal inflammation caused by other illnesses, bowel wall perfusion in preterm neonates to predict developing necrotizing enterocolitis, or in children with small bowel obstruction for the detection of strangulation (8,14,15). In the present study we intended to evaluate SMA blood flow hemodynamics after surgery and found low values of SMA BFV, PSV, and RI when assessed with the cut-off values given in the literature (6)(7)(8). We suggest that decreased blood flow in the SMA in patients with midgut volvulus may be related to congenital abnormality in anatomy such as a shortened mesenteric root and/or decreased intestinal length after resection.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…2 However, there has been little literature on pediatric vascular ultrasounds except very few case reports. 3–8 These case reports demonstrate the utility of ultrasounds to evaluate different types of vascular pathologies in pediatric patients including portal vein thrombosis, arterial aneurysm, vascular malformation, and deep vein thrombosis of the extremities; however, even though ultrasonography is used to diagnose the pathology, no literature reports the positive finding rate of the examinations. 9 The purpose of this study is to distinguish whether or not there would be a higher rate of positive findings in the pediatric population in comparison to the adult population.…”
Section: Introductionmentioning
confidence: 99%